Should I stay or should I go? Migration intentions of teenagers with parents working abroad - Joanna Clifton-Sprigg (Journal of Applied Economics, 2022)
This paper investigates how having a parent working abroad affects subsequent intentions of teenagers to emigrate, using unique data for Poland. Results show that parental employment abroad is positively associated with children's intentions to emigrate, more so for males than females. The findings highlight the intergenerational nature of migratory trends within families. This is particularly important for a country like Poland, which alongside other Central and Eastern European economies, has been experiencing significant population outflows for almost two decades and is gradually turning towards a foreign-born workforce.
Keywords: 330; migrant parents; Migration intentions; young people